2015
DOI: 10.1155/2015/146306
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Duration of Staying Free from Acquiring Rehappening Opportunistic Infections among Pre-ART People Living with HIV/AIDS between 2008 and 2013

Abstract: Introduction. In regional state of the study area, HIV (Human Immunodeficiency Virus) prevalence is 2.2% and opportunistic infections (OIs) occurred in 88.9% of pre-ART (Antiretroviral Therapy) people living with HIV/AIDS (PLWHA). Even though OIs are prevalent in the study area, duration of staying free from acquiring rehappening opportunistic infections and its determinant factors are not studied. Method. The study was conducted in randomly selected 341 adult Pre-ART PLWHA who are included in chronic HIV care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…These factors coupled with individual immune status will increase their chances of contracting an opportunistic infection. Even though OIs are prevalent in this study, duration of staying free from acquiring rehappening opportunistic infections and its determinant factors are merely mentioned and state of mind due to factors like divorce can contribute (24). As expected, study results show that those with income below Kshs 5000 were the most affected with OIs.…”
Section: Prevalence Of Opportunistic Infectionsmentioning
confidence: 46%
“…These factors coupled with individual immune status will increase their chances of contracting an opportunistic infection. Even though OIs are prevalent in this study, duration of staying free from acquiring rehappening opportunistic infections and its determinant factors are merely mentioned and state of mind due to factors like divorce can contribute (24). As expected, study results show that those with income below Kshs 5000 were the most affected with OIs.…”
Section: Prevalence Of Opportunistic Infectionsmentioning
confidence: 46%
“…In this study, community-acquired pneumonia (41.5%) was the most common OI, followed by pulmonary tuberculosis (22.2%). In contrast, pulmonary tuberculosis was the most common OI compared to other studies conducted in Ethiopia including St. Hospital, Paul's Millennium Medical College, Addis Ababa (43.49%) (41), and Ayder Referral Hospital, Mekelle (32.3%) (32). The fact that the incidence of tuberculosis was lower just after community-acquired pneumonia may be attributable to the intensified tuberculosis screening program and the provision of IPT, which was more than 80% in this study.…”
Section: Discussionmentioning
confidence: 83%
“…Compelling evidence supporting the current finding was reported in other studies ( 43 – 46 ). In addition, a retrospective cohort study by Bizuayehu et al revealed that the hazards of OIs were reduced by 69% in adult patients with HIV who took CPT ( 44 ). The Ethiopian ART guideline recommends initiating trimethoprim–sulfamethoxazole as the primary prevention of PCP, toxoplasmosis, bacterial infections, malaria, and diarrhea caused by Isospora belli or Cyclospora species.…”
Section: Discussionmentioning
confidence: 99%
“…Segundo, la fase crónica en la que el paciente puede mostrar síntomas como fiebre, tos seca, diarrea, sudoración… (Iglesias Villarán et al, 2015;Rodríguez & Moreno.II, 2017;Sandí & Chan, 2016;Valle et al, 2018). Por último, en caso de que la enfermedad no se trate adecuadamente, puede desembocar en Síndrome de Inmunodeficiencia Adquirida o SIDA caracterizada por presentar cánceres o infecciones oportunistas como la neumonía, la salmonerosis, la candidiasis o la tuberculosis (Bizuayehu et al, 2015;WHO, 2017).…”
Section: Introductionunclassified